O documentário como produção jornalística: nos limites da pesquisa experimental em trabalhos de conclusão em jornalismo - Pinto, Cíntia Xavier da Silva (Universidade do Vale do Rio dos Sinos, 2011)
This text presents the results of the research which observes audiovisual materials produced at Journalism undergraduate courses as completion works. In the intention of the research, we verify how the videos are understood in the crossing between journalism and documentary. The audiovisual materials are communication products which use the notion of documentary as approach and argument of built reality. In this line, journalism has strategies of approaching of social reality to produce the journalistic events. To build stories, the videos produced at undergraduate courses use or not using such strategies both of documentary and of journalism. To reach to components of analysis of the videos produced at undergraduate courses, we work with concepts of documentary from practice, tradition and technological development as way of transformation of the act to argue about reality. In turn, journalism is grasped from specific elements, like: public interest, plurality of voices, sources, event, interview and reportage. We recognize close characteristics between documentary and audiovisual reportage: the practice of television reportage, through elements as moving image, record equipaments, framing of image and edition. The three mentioned axles, documentary concept, elements of journalism and constitution of television reportage, help to understand the videos observed. The corpus of analysis consists of 14 videos obtained at the institutions: PUC-Minas (one video), UFBA (five videos), UFPE (one video), UEPG (three videos), Unibrasil (one video) and USP (three videos). For the analysis of videos, we carry out a interested description of the videos. With the description, we obtained information about regulations for experimental projects and interviews with supervisors. In analysis, we verify the existence of videos with etnographic character, in which students seek reversions of common ways of covering of events. We point as result the adoption of interview as standard procedure of the documentaries studied. Other relevant data is the using of not official sources in documentaries, much more than the official sources. The official sources are used more widely in daily journalism. Finally, the adopted approaches in the videos are guided to social problems or less discussed in mainstream media.
Keywords: Jornalismo; Documentário; Projeto experimental; Reportagem; Journalism; Documentary; Experimental project; Audiovisual reportage; ACCNPQ::Ciências Sociais Aplicadas::Comunicação